2001
DOI: 10.1097/00006842-200107000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Stress Response Inventory and Its Application in Clinical Practice

Abstract: These results indicate that the SRI is highly reliable and valid, and that it can be utilized as an effective measure of stress for research in stress-related fields. The depressive disorder group showed more prominent stress responses than the anxiety and psychosomatic disorder groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
2
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 10 publications
2
108
2
3
Order By: Relevance
“…First, stress score measurements were self-reported, and were therefore subject to bias. Here, the women reported more subjective stress than did the men, and the women's average stress score was higher than that of the men; these results parallel those of previous studies indicating that women perceive stress more intensely than men (Koh et al, 2001), and that the incidence of depressive disorders is higher in women than in men (Piccinelli and Wilkinson, 2000). Thus, the bias associated with selfreport in the current study may be negligible.…”
Section: Discussionsupporting
confidence: 88%
“…First, stress score measurements were self-reported, and were therefore subject to bias. Here, the women reported more subjective stress than did the men, and the women's average stress score was higher than that of the men; these results parallel those of previous studies indicating that women perceive stress more intensely than men (Koh et al, 2001), and that the incidence of depressive disorders is higher in women than in men (Piccinelli and Wilkinson, 2000). Thus, the bias associated with selfreport in the current study may be negligible.…”
Section: Discussionsupporting
confidence: 88%
“…Prolonged exposure to stressors is signaled by alterations in cytokine profile, such as increasing IL1 and TNF␣, and decreasing IL2. 22 Psychological involvement was gauged by a battery of questionnaires providing self-rated scales that, in line with previous 23 and more recent studies, 24 focuses on appraisal, coping, and health. In brief, we assessed the following factors: 25 • the appraisal of stress, tiredness, or activation by a global scoring index (0 -30) • coping by a graphic questionnaire (scores 0 -10), exploring in particular the dimension of control • somatic complaints by a symptoms' list that furnishes a global scoring index (scores 0 -50).…”
Section: Assessment Of Overall Stress Levelmentioning
confidence: 96%
“…Respondents did not find the self-score scales posed any specific problems. Several studies have examined the reliability and validity of self-rating scales (Koh et al, 2001;Voruganti et al, 1998;Weaver et al, 2003) and found them to be acceptable. Confidence is a subjective experience that is impossible to measure in a manner homogenous to the study group.…”
Section: Study Response Ratementioning
confidence: 99%